Flower-like NiO nanostructures synthesized by electrodeposition method for efficient detection of toluene gas. Issue 112 (27th October 2015) - Yuan, Chaoxin; Li, Hairong; Xie, Longzhen; Wang, Fang; Deng, Heng; Chang, Fangzhi; Sun, Yongzhe
Abstract : The technological process for the preparation of nickel oxide nanomaterials in this work. Abstract : Nickel oxide (NiO) flower-like hierarchical nanostructures were obtained by electrodeposition and oxidation methods. The surface morphology and structure of the fabricated NiO were examined by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The gas sensing characteristics toward toluene gas are investigated. The sensors based on this nanostructures exhibit a high response to 5 parts-per-million (ppm) of toluene (ratio of resistance to gas and air = 2.63) under an operating temperature of 250 °C. Furthermore, the response and recovery time to 2 ppm can reach 13.6 s and 24.5 s, respectively. The results indicate that the flower-like nanostructure is a potential candidate for gas sensors with good performances for practical applications.